(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Fuels derived from petroleum are becoming increasingly scarce and expensive. A shortage of petroleum products is likely if the current trend continues. Finding sustainable energy sources could help alleviate this issue to a large extent. Biodiesels, made from a wide variety of vegetable oils, are a viable alternative. The purpose of this research was to evaluate the efficiency and emissions of a four-stroke diesel engine using Mahua biodiesel and Cotton seed biodiesel blended with diesel as a replacement fuel. The performance of the engine with biodiesel blend B20 as fuel is compared with the diesel fuel on the basis of brake specific fuel consumption, brake thermal efficiency, exhaust gas temperature and emissions of hydrocarbons and oxides of nitrogen. Based on the results of this research, the engine’s performance with these biodiesel blends is similar to that of diesel, but the emissions of hydrocarbons are lower. The performance and emission characteristics of biodiesel blends made from cotton seed are superior than those made from Mahua biodiesel, it has been discovered.